Soil Factor Affecting the Natural Regeneration of Silver Fir and Spruce in Himachal Pradesh - Jha, M. N.; Rathore, R. K.; Pande, P. (Indian Forester, 1984)
Soils and their behaviour with respect to natural regeneration of fir and spruce in Narkanda (Himachal Pradesh) were studied. Soil formation is predominantly governed by podzolization process but the soli propi1e in poorly regenerated area shows almost negligible eluviation of clay and organic matter due to fairly well developed 'O' horizon. The soils are distinctly acidic, unsaturated and possess low cation exchange capacity. It is likely that the hydrophobic substance released from the decomposition of litter of fir and spruce severely restricted the wetting of the soil Therefore, the insufficient moisture content in the soil due to this thick layer of bumus on tbe surface affected the process of natural regeneration of fir and spruce in Narkanda.